Integrated morphological and biochemical analysis of selected sesame (Sesamum spp.) species - V. P., Varadha Gayathri; B., Lovely; K., Arya; Jayapal, Atul; Gopinath, Pratheesh P. (Frontiers in Plant Science, 2025)
The study aimed to characterize wild relatives and traditional cultivars of sesame based on their morphology and biochemical properties, including crude protein, oil content, fatty acid profiles, and total phenol content. The study included accessions of Sesamum indicum, S. radiatum, S. mulayanum, and S. malabaricum. A comparative analysis revealed significant variation in flower color among the species. S. indicum had pale purplish-pink flowers, while S. mulayanum and S. malabaricum had dark violet flowers, and S. radiatum had white flowers with violet borders. Differences in capsule hairiness were also noted, with cultivated species having glabrous capsules, while wild species exhibited hairy capsules. The hairiness ranged from weakly hairy capsules in S. mulayanum and S. malabaricum to strongly hairy capsules in S. radiatum. All 27 genotypes produced a single flower per axil, a trait common across all sesame species. The S. indicum accession, Ayali 1, produced the most capsules per plant, while S. radiatum (IC 256273) produced the fewest. S. radiatum accessions had the longest and broadest capsules, while the shortest and narrowest capsules were found in S. malabaricum. Cultivated sesame varieties produced larger and heavier seeds compared to wild species. The highest phenol content was recorded in S. radiatum (IC 210433), while the lowest was observed in Kayamkulam 1. Seed yield per plant showed a strong positive correlation with the number of capsules per plant, 1000 seed weight, and oil content, while a significant negative correlation was found between phenol content, plant height, and seed yield. Oil content analysis revealed that the highest oil yield came from Thilak seeds, while the lowest yield was observed in S. malabaricum (IC 557243). Fatty acid profiling showed the presence of both saturated fatty acids (palmitic acid, stearic acid, behenic acid, margaric acid, and arachidic acid) and unsaturated fatty acids (oleic acid, linoleic acid, linolenic acid, eicosanoic acid, 11-eicosenoic acid, and linolelaidic acid) in varying proportions across sesame samples.